Characteristics of national and major regional percutaneous coronary intervention registries: A structured literature review - Biswas, S.; Lefkovits, J.; Liew, D.; Gale, C.; Reid, Christopher; Stub, D. (2018)
Aims: Clinical registries have a growing role in the assessment of healthcare quality and safety. It is unclear, however, how many countries utilise registries for patients who receive percutaneous coronary intervention (PCI). The aim of this review was to provide an overview of the characteristics of PCI registries from around the world. Methods and results: A systematic search of the published and online grey literature was undertaken to identify currently active national PCI registries. In countries without a national PCI registry, the three largest regional registries were included. Thirty registries in 26 countries that met inclusion criteria were identified, of which 24 (80%) are national registries and six (20%) are regional registries. Fourteen registries (47%) collect 30-day mortality rates while 11 registries (37%) collect 12-month mortality rates. Nine registries (30%) provide risk-adjusted mortality rates and 16 registries (53%) report bleeding outcomes, utilising a variety of bleeding definitions. Thirteen registries (43%) publicly report key quality metrics. Conclusions: There is substantial geographic variation in the distribution of PCI registries. Comparison across registries is challenging due to varying data definitions and collection time points. Public reporting of outcomes data is being increasingly implemented by PCI registries, but risk-adjustment models remain underutilised.